Integrasi Nilai Pendidikan Sosial pada Kirab Tutup Suro dalam Bingkai Moderasi Beragama di Ponorogo - Muhaimin, M. Zunaidul; Zuhriyah, Nunik (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The tradition of Kirab Tutup Suro, teaches people to have a sense of mutual cooperation. The purpose of this research is to know the biganning of story and the procession of kirab tutup suro in ponorogo and understand the values of social education contained in the activities of tutup suro in Ponorogo. The research method uses field research with the type of case study research, the object studied is the old city residents. data collection methods using interviews, observation and documentation. The results showed, 1) the tradition of kirab tutup suro originated from a story that developed in Ponorogo began when the King of Kediri was seeking knowledge to Mount Lawu met Ki Joko Bujang, 2) Implementation of the book of tutup suro there are two stages beginning and core implementation, 3) the values obtained in the kirab tutup Suro are mutual cooperation and the establishment of good relationship.Keywords: Kirab Tutup Suro, Social Education, Religious Moderation.